Investigating Factors Influencing the Purchasing Intention of Electric Vehicles among Rural Thai Consumers - Ariyamongkolcharoen, Nutthanan; Prachansit, Tayakorn; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – The purpose of this research is to analyze the significant influence of environmental concern, social influence, performance expectancy, attitude toward EV innovation toward purchasing EV car intention. Design/Methodology/Approach – The research employs primary and secondary data collection methods to conduct an analysis among factors influencing EV car purchasing intentions. The data was collected among 390 respondents who are interested in EV cars and live in upcountry of Thailand. This research referenced three theoretical frameworks from previous studies for conducting a new conceptual framework. Findings – This research is intended to investigate factors influencing Electric Vehicles Purchasing Intention of Thai People in Upcountry. Followed by the findings of this research represented environmental concern, social influence and performance expectancy which have relationships toward attitude toward EV innovation. Lastly, attitude toward EV innovation directly influence EV car purchase intention. Research Limitations/Implications – The limitations of the research displayed several elements limit among factors influencing Electric Vehicles Purchasing Intention of Thai People in Upcountry. The scope of this study focused only on purchasing intentions of Thai People in Upcountry. Moreover, this research focused on the people who have experience with electric car and interest on electric car. Originality/value – This research focuses on significant factors influencing Electric Vehicles Purchasing Intention of Thai People in Upcountry. Keywords – Environmental concern, Purchase intention, Social influence, Performance expectancy, attitude toward EV innovation JEL classification code – O13, O18, O32